DOCUMENT: a system for classifying drug-related problems in community pharmacy - Williams, M.; Peterson, G.; Tenni, P.; Bindoff, I.; Stafford, Andrew (Springer Science + Business Media, 2011)
Background: Drug-related problems (DRPs) are a major burden on the Australian healthcare system. Community pharmacists are in an ideal position to detect, prevent, and resolve these DRPs. Objective: To develop and validate an easy-to-use documentation system for pharmacists to classify and record DRPs, and to investigate the nature and frequency of clinical interventions undertaken by Australian community pharmacists to prevent or resolve them. Setting: Australian community pharmacies. Method: The DOCUMENT classification system was developed, validated and refined during two pilot studies. The system was then incorporated into software installed in 185 Australian pharmacies to record DRPs and clinical interventions undertaken by pharmacists during a 12-week trial. Main outcome measure: The number and nature of DRPs detected within Australian community pharmacies. Results: A total of 5,948 DRPs and clinical interventions were documented from 2,013,923 prescriptions dispensed during the trial (intervention frequency 0.3%). Interventions were commonly related to Drug selection problems (30.7%) or Educational issues (23.7%). Pharmacists made an average of 1.6 recommendations per intervention, commonly relating to A change in therapy (40.1%) and Provision of information (34.7%). Almost half of interventions (42.6%) were classified by recording pharmacists as being at a higher level of clinical significance. Conclusion: The DOCUMENT system provided pharmacists with a useful and easy-to-use tool for recording DRPs and clinical interventions. Results from the trial have provided a better understanding of the frequency and nature of clinical interventions performed in Australian community pharmacies, and lead to a national implementation of the system.